An Application of Differential Transform Method to Solve an Epidemic Model — Ebola Virus Disease Outbreaks - Preethi, G. Tamil; Magesh, N. (Communications in Mathematics and Applications, 2023)
An epidemic is defined as an unusually large, short-term disease outbreak. Various factors influence a disease’s spread from person to person. These include the infectious again itself, its mode of transmission, infectious period and its susceptibility and resistance. In this work, we consider a system of non-linear differential equations which constructed as a mathematical model of disease due to Ebola Virus Disease. This model is divided into five compartments as SIRDP (SusceptibleInfected-Recovered-Deceased-Pathogens). Further, we solve this model by one of the novel techniques the Differential Transform Method (DTM). Moreover, the simulation of solution derived by DTM is compared with VIM.
Keywords: Ebola Virus Disease (EVD); Differential transform method; Variational iteration method